Antioxidant and anticancer activities of polyphenolic compounds from three Acanthaceae medicinal species from Burkina Faso - Ouattara Nabèrè; Guenné Samson; Hilou Adama; Compaoré Moussa; Sombié P.A.D. Eric; Nacoulma P. Aminata; Millogo-Rasolodimby Jeanne; Nacoulma Odile Germaine (International Journal of Phytomedicine, 2012)
Phytochemical screening and biological activities of methanol extracts from three Acanthaceae species namely Hygrophila auriculata (H. auriculata), Nelsonia canescens (N. canescens) and Peristrophe bicalyculata (P. bicalyculata), widely used in local ethnomedicine, were carried out. Phenolic content quantification indicated that H. auriculata extract possessed the highest polyphenolics content followed by N. canescens and P. bicalyculata. Biological activities assessment showed that H. auriculata extract has the best antioxidant (through DPPH, FRAP and ABTS methods) capacity. Acetylcholinesterase and Lipoxygenase inhibition tests revealed interesting activities from P. bicalyculata. Testing cancer cells antiproliferation, it was showed that H. auriculata and N. canescens) were of good interest (27.00±1.55 and 29.70±3.11 µg/mL). These results showed that the phenolic compounds of these plants could justify their local traditional use to treat inflammatory and tumoral diseases.